Smiles when sharing - Mehu, M; Grammer, K; Dunbar, R (Elsevier, 2007)
One of the proposed functions of human smiling is the advertise cooperative dispositions and thereby increase the likelihood that a social partner would invest resources in a relationship. In particular, smiles involving an emotional component would be honest signals of altruistic dispositions because they are not easy to produce voluntarily. In this study, 60 people were covertly filmed while interacting with a friend in two conditions: control and sharing. Smiles were classified into Duchenne (spontaneous) and non-Duchenne smiles. Participants also completed a series of questionnaires, including the Altruism Scale and a self-report questionnaire of emotional state. Interestingly, Duchenne smiles were displayed at higher rates in the sharing situation as opposed to the control situation, whereas non-Duchenne smiles were unaffected by the type of interaction. Furthermore, Duchenne smiles in the sharing interaction were positively affected by a measure of altruism. Self-reported emotional states did not vary between conditions and were poorly related to smiling. This study shows that the Duchenne smile is relevant to situations that involve the sharing of material resources because it would reliably advertise altruistic intentions. The Duchenne smile could therefore be an important signal in the formation and maintenance of cooperative relationships.